Rhythms of recovery : trauma, nature, and the body - Korn, Leslie E. (New York, NY : Routledge, 2022)
"The classic edition of Rhythms of Recovery sheds light on rhythm, one of the most important components of our survival and well-being. It governs the patterns of our sleep and respiration and is profoundly tied to our relationships with friends and family. But what happens when these rhythms are disrupted by traumatic events? Can balance be restored, and if so, how? What insights do eastern, natural, and modern western healing traditions have to offer, and how can practitioners put these lessons to use? Is it possible to do this in a way that's culturally sensitive, multidisciplinary, and grounded in research? Rhythms of Recovery examines and answers these questions and provides clinicians with effective, time-tested tools for alleviating the destabilizing effects of traumatic events. It also explores integrative medicine, East/West medicine, herbal medicine, psychedelic medicine, complex trauma, yoga, and somatic and feminist therapies. For practitioners and students interested in integrating the insights of complementary/alternative medicine and 21st-century science, this deeply appealing book is an ideal guide"--
Keywords: Biological rhythms; Chronobiology; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychopathology / Post-Traumatic Stress Disorder (PTSD); PSYCHOLOGY / Psychotherapy / General